Nadia knows best - Mansell, Jill (Sourcebooks Landmark, 2012)
When Nadia meets Jay, she's tempted. Stranded together while a snowstorm rages outside-- who would ever know? But when you belong to a family like the Kinsellas, someone has to exercise a bit of self-control, don't they? Nadia wouldn't want to do something she might regret later...